Vegetation dynamics of Sangkub watershed in North Sulawesi Province indicated by NDVI of Landsat data - Veybi Djoharam; Widiatmaka Widiatmaka; Marimin Marimin; Dyah Retno Panuju; Suria Darma Tarigan (Journal of Degraded and Mining Lands Management, 2022)
Vegetation can be an important indicator of ecosystem change, the influence of anthropogenic and non-anthropogenic factors. Therefore, it is important to study the dynamics of vegetation changes. One technique that can be used for vegetation analysis is the Normalized Difference Vegetation Index (NDVI). NDVI is an indicator of the active biomass that helps distinguish vegetation from other land cover and can provide information about changes in Spatio-temporal vegetation dynamics, thus allowing for assessment of the ecological conditions. This study aimed to investigate the dynamic of vegetation in the Sangkub watershed area located in North Sulawesi Province. This analysis used geospatial technology with the NDVI method, utilizing Landsat 5 and Landsat 8 satellite imagery data in three periods the year 2000, 2015, and 2020. The results showed that vegetation cover of the Sangkub watershed decreased substantially, whereas the non-vegetated area increased gradually over time.